Exploring the potential of humanin as a biomarker for early breast cancer detection: a study of serum levels and diagnostic performance - Hekim, Munevver Gizem; Ozcan, Sibel; Yur, Mesut; Yildirim, Nilgun; Ozcan, Mete (Taylor & Francis Ltd, 2023)
IntroductionBreast cancer is a leading cause of cancer death in women worldwide, and early detection is crucial for effective treatment. Mitochondrial dysfunction has been linked to cancer development and progression. Humanin, a mitochondrial-derived peptide, has been shown to have cytoprotective effects and may be involved in breast cancer development. In this study, we aimed to investigate the potential of humanin as a biomarker for breast cancer.MethodsWe recruited 45 female patients diagnosed with primary invasive ductal breast cancer and 45 healthy volunteers. Serum humanin levels were measured using ELISA, and other cancer markers were measured using an Advia Centaur Immunology Analyser.ResultsOur results showed that serum humanin levels were significantly higher in breast cancer patients than in healthy controls (p = 0.008). ROC curve analysis indicated that humanin could effectively discriminate between patients and healthy individuals, with a sensitivity of 62.5% and a specificity of 77.5%.ConclusionThis suggests that humanin may be a potential new biomarker for breast cancer screening and early detection. Further research is needed to fully understand the relationship between humanin and breast cancer and to develop new diagnostic and therapeutic strategies.
Keywords: Humanin; breast cancer; mitochondrial dysfunction; biomarker; diagnosis; >